ANALISIS KELAYAKAN FINANSIAL PABRIK KELAPA SAWIT DI PT. SURYARAYA LESTARI 2 KABUPATEN MAMUJU TENGAH PROVINSI SULAWESI BARAT - Ni Made Ayu Septirini; Agus Santosa; Ni Made Suyastiri YP (Jurnal Dinamika Sosial Ekonomi, 2015)
The purpose of this study is to analyze the financial feasibility conducted by PT SURYARAYA LESTARI 2. The method of implementation research is a case study. Financial analysis criteria used in this study are Net Present Value(NPV), Internal Rate of Return(IRR), and Payback Period(PBP). The results showed that PT. SRL2 feasible to run with the results of its NPV is Rp 107,424,520,162; IRR of 17.01%, and payback period is 4 years